Influence of Training, Work Discipline, and Motivation on Organizational Performance (A Case Study of Members of Samsat, The West Jakarta Regional Police) - Bonifacius, Anggi Putra; Pasaribu, Bomer; Hoesin, Wagiarto (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
This study aims to analyze the effect of training, work discipline, through motivation on the performance of members of Samsat, the West Jakarta area. With the results of the data obtained that happened to members of the West Jakarta’s Samsat, namely that training goals and objectives were still not achieved, there was still a lack of work discipline, a lack of motivation to prioritize office work which caused delays in completing assignments, performance results that did not meet the target expected by the agency with complaints from the public. The sampling collection technique used was purposive sampling method where the sampling was taken from the largest population, namely 77 members of the police. The data analysis used was path analysis. The conclusion from this study is that training, work discipline, and motivation directly affect member performance, but indirectly motivation has a greater effect on the performance of West Jakarta’s Samsat members. This shows that work motivation is an intervening variable then it can shape the performance desired by the agency.